Preliminary qualitative analysis on mtDNA in Astyanax fasciatus populations Cuvier, 1819 (Teleostei; Characidae) indicate population distinctiveness - Matoso, Daniele Aparecida; Martins, Cesar [UNESP]; Artoni, Roberto Ferreira; Galetti Jr, Pedro Manoel (Brazilian Archives of Biology and Technology, 2010)
Uma análise qualitativa da variabilidade genética em Astyanax fasciatus (Cuvier, 1819) do alto Rio Tibagi e Parque Estadual de Vila Velha (PEVV) foi conduzida por digestão enzimática (RFLP) da região D-Loop do mtDNA. Os resultados evidenciaram que essas populações são geneticamente diferentes.

A preliminary qualitative analysis of genetic variability status in Astyanax fasciatus (Cuvier, 1819) from upper Tibagi River headwaters and Vila Velha State Park (VVSP) was carried out by enzymatic digestion (RFLP) of D-Loop region from mtDNA. The results showed that Tibagi and VVSP populations were genetically different.
Keywords: Neotropical fish; RFLP; conservation genetics